Lactobacillus amylovorus Inhibits the TLR4 Inflammatory Signaling Triggered by Enterotoxigenic Escherichia coli via Modulation of the Negative Regulators and Involvement of TLR2 in Intestinal Caco-2 Cells and Pig Explants - Finamore, Alberto; Roselli, Marianna; Imbinto, Ambra; Seeboth, Julie; Oswald, Isabelle P.; Mengheri, Elena (PloS one, 2014)
Inflammation derived from pathogen infection involves the activation of toll-like receptor (TLR) signaling. Despite the established immunomodulatory activities of probiotics, studies relating the ability of such bacteria to inhibit the TLR signaling pathways are limited or controversial. In a previous study we showed that Lactobacillus amylovorus DSM 16698T, a novel lactobacillus isolated from unweaned pigs, protects the intestinal cells from enterotoxigenic Escherichia coli (ETEC) K88 infection through cytokine regulation. In the present study we investigated whether the ability of L. amylovorus to counteract the inflammatory status triggered by ETEC in intestine is elicited through inhibition of the TLR4 signaling pathway. We used the human intestinal Caco-2/TC7 cells and intestinal explants isolated from 5 week-old crossbreed Pietrain/Duroc/Large-White piglets, treated with ETEC, L. amylovorus or L. amylovorus cell free supernatant, either alone or simultaneously with ETEC. Western blot analysis showed that L. amylovorus and its cell free supernatant suppress the activation of the different steps of TLR4 signaling in Caco-2/TC7 cells and pig explants, by inhibiting the ETEC induced increase in the level of TLR4 and MyD88, the phosphorylation of the IKKα, IKKβ, IκBα and NF-κB subunit p65, as well as the over-production of inflammatory cytokines IL-8 and IL-1β. The immunofluorescence analysis confirms the lack of phospho-p65 translocation into the nucleus. These anti-inflammatory effects are achieved through modulation of the negative regulators Tollip and IRAK-M. We also found that L. amylovorus blocks the up-regulation of the extracellular heat shock protein (Hsp)72 and Hsp90, that are critical for TLR4 function. By using anti-TLR2 antibody, we demonstrate that TLR2 is required for the suppression of TLR4 signaling activation. These results may contribute to develop therapeutic interventions using L. amylovorus in intestinal disorders of piglets and humans.